The authigenic dolomite and smectite formations in the Neogene lacustrine-fluvial Caybagi Basin (Elazig, Eastern Turkey) - Akkoca, DB; Sagiroglu, A (Slovak Acad Sciences, Earth Science Inst, 2005)
Mineralogical studies (XRD, SEM, EDS) and geochemical analysis (XRF) were. applied to samples of the Neogene Caybagi Formation representing different facies of lacustrine and fluvial lithologies. The bulk mineralogy of the fluvial and lacustrine deposits comprises carbonate minerals (calcite, dolomite, aragonite), clay minerals (smectite, illite, chlorite, mixed-layer clays S-C), nonclay silica minerals (quartz, feldspars, opal, cristobalite) and gypsum and anhydrite. The smectite, calcite, dolomite and gypsum are generally authigenic. The quartz, feldspar, illite, chlorite, detrital smectite probably derived from basement rocks. Major oxides and trace elements (SiO2, TiO2, Al(2)O3, Fe2O3, Cr, Ni, Co, Cu) are present in high amounts in the fluvial formations and the marginal lacustrine facies, and these are constituents of detritics transformed from the surrounding basement. The central facies of the lacustrine formations are rich in Ph, Ba, Rb, Sr, CaO and K2O and composed of authigenic limestone, dolomite, gypsum, anhydrite. and smectite. The authigenic minerals are probably derivatives of the solutions solved from clastics and ash fall and moved towards the central zones of the lake increasing pH, Mg/Ca ratios and thus leading to the precipitation of the carbonate. The high Ba/Sr and Rb/Sr ratios in marginal lake facies; are related to the presence of small amounts of carbonates, which incorporated Sr.
Keywords: neogene; Eastern Turkey; lacustrine and fluvial deposits; geochemistry; clay mineralogy